Migration and dementia: a meta-analysis of epidemiological studies in Europe. Issue 11 (8th August 2021) - Selten, Jean-Paul; Termorshuizen, Fabian; van Sonsbeek, Maarten; Bogers, Jan; Schmand, Ben
Abstract: Background: To provide an overview of epidemiological studies of dementia among migrant groups in Europe and to estimate their pooled odds ratio (OR) v. the reference population. Methods: Search for articles reporting on incidence or prevalence of dementia among ethnic minorities and migrants in Europe, published before 21 December 2018. We performed several meta-analyses, using a random-effects model, and, when there was no evidence of heterogeneity, a fixed-effects model. We distinguished between all migrants, African-Europeans and Asian-Europeans. Results: We retrieved five population-based surveys and two health care record studies. The latter included one incidence study, the remainder were prevalence studies. The meta-analysis of all studies yielded a pooled OR, adjusted for age and sex, of 1.73 (95% CI 1.42–2.11) for dementia in all migrant groups. However, the pooled OR of population surveys (3.10; 95% CI 2.12–4.51) was significantly higher than that for the health care record studies (OR 0.94; 95% CI 0.80–1.11). The pooled ORs for African-Europeans and Asian-Europeans, based on population surveys, were 2.54 (95% CI 1.70–3.80) and 5.36 (95% CI 2.78–10.31), respectively. Conclusions: The discrepancy between health care record studies and population surveys suggests that many migrants remain undiagnosed. Migrants from Asia and Africa seem to be at significantly increased risk of dementia in Europe. Since the prevalence rates in their countries of origin are generally not higher than those for natives in Europe, there may be a parallel with the epidemiology of schizophrenia.